Study of Some Organic Superconductors Using BCS-Theory - Singh, M.P.; Mishra, L.K. (Asian Journal of Chemistry, 2010)
Using the conventional phonon exchange mechanism of superconductivity, we have succeeded in reproducing the transition temperature Tc of some newly discovered organic superconductors by introducing certain modifications to the well known BCS-formulae for Tc. Taking the value of density of states at the Fermi surface, N(o), calculated from d.c. paramagnetic measurement, the values of Δo(o) and Hc(o) have been evaluated in the weak coupling limit.